2021
DOI: 10.1186/s13059-021-02381-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA mutations in Arabidopsis plants after multigenerational exposure to high temperatures

Abstract: Background Elevated temperatures can cause physiological, biochemical, and molecular responses in plants that can greatly affect their growth and development. Mutations are the most fundamental force driving biological evolution. However, how long-term elevations in temperature influence the accumulation of mutations in plants remains unknown. Results Multigenerational exposure of Arabidopsis MA (mutation accumulation) lines and MA populations to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 91 publications
4
48
3
Order By: Relevance
“…For the three sets of SNP comparisons in P. wickerhamii, 59.87%, 61.91%, and 58.60% were transitions in S1 vs. S931, S1 vs. ATCC 16529, and ATCC 16529 vs. S931, respectively, and the rate of transitions was higher than that of transversions (transition/transversion ratios ranged from 1.415 to 1.625) (Table S13). The SNP C/T was the most common (~30%) and A/T the least common (below 7.3%) substitution observed, which is different in comparison to findings in higher plant species (Lu et al, 2021).…”
Section: Comparative Genomics and Putatively Involved In Pathogenicit...contrasting
confidence: 94%
“…For the three sets of SNP comparisons in P. wickerhamii, 59.87%, 61.91%, and 58.60% were transitions in S1 vs. S931, S1 vs. ATCC 16529, and ATCC 16529 vs. S931, respectively, and the rate of transitions was higher than that of transversions (transition/transversion ratios ranged from 1.415 to 1.625) (Table S13). The SNP C/T was the most common (~30%) and A/T the least common (below 7.3%) substitution observed, which is different in comparison to findings in higher plant species (Lu et al, 2021).…”
Section: Comparative Genomics and Putatively Involved In Pathogenicit...contrasting
confidence: 94%
“…Genome sequencing has several applications in plant stress science. The structural analysis of DNA is not only fundamental for classifying organisms but also for identifying stress-driven mutations, which occur in plants under heat [ 46 ], drought [ 47 ], and other abiotic stresses [ 48 ]. Moreover, DNA structural variations occurring under low-dose stress can be linked to gene function using gene ontology analyses to reveal the genetic basis of hormesis [ 49 ].…”
Section: Data In Plant Hormesis Researchmentioning
confidence: 99%
“…This, to some extent, reveals a genome-selective (GS)-dependent approach that can control interactions between plants and high temperatures [ 13 ]. Lu and colleagues then found that after exposure to extreme heat and moderate warming, mutation rates of single-nucleotide variations (SNVs) and small indoles were increased in Arabidopsis thaliana multigenerational accumulation plants, which is associated with changes in epigenetic modifications, such as DNA methylation levels [ 18 ]. These studies and advances provide insights and guidance on genetic and epigenetic structures as well as correlations between different biological traits (i.e., yield and growth-dependent biomass) under high temperature stress.…”
Section: Emerging Strategies In Vegetable Practice Managementmentioning
confidence: 99%
“…Epigenetic modification enriches the diversity of genetic information in vegetable crops [ 19 ]. The evolution of heat-induced SNPs accumulation is dynamically regulated by DNA methylation [ 18 ], suggesting that epigenetic modification and environmentally induced SNP-dependent genetic selection should be considered synergistically [ 13 ].…”
Section: Emerging Strategies In Vegetable Practice Managementmentioning
confidence: 99%